Investigation of Road Pavement Failures Using Active and Passive Surface Wave Methods in Parts of Calabar Municipality, Cross River State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2023)
The active and the passive techniques of surface wave were employed to investigate some major road pavement failures within the Calabar metropolis, Cross River State. The dispersion curves from MASW (active) and ReMi (passive) were inverted to give a 1D shear wave velocity model. The aim of this study was to comparatively investigate the major causes of the incessant road pavement failures especially few months after its construction and repairs within the study area using the shear wave velocity and blow count (N values). These roads are all located within the same geologic setting of the Calabar Coastal Plan Sand and showed evidence of road failures ranging from pot holes, alligator cracking, rutting and shear failure cracking etc. For each site, two sets of data were collected; the Passive and the Active seismic surface wave data. The survey was able to gather the following data from each location; shear wave velocity, primary wave velocity, N-values for both the active and the passive data which were both derived by the Seisimager surface wave software. The software was used to delineate low velocity layers within the depth of 4m – 6m at the failed portions of the survey sites exception of location 1 (the control site) which showed an ideal situation of increasing velocity with depth. These low velocity layers were inferred to be the major cause of the incessant failure of the pavements in the survey areas. These velocities and the N- values (blow count) were used to classify each location into sites C, D and E, according to the 1997 National Earthquake Hazards Reduction Program (NEHRP).